Effectiveness of AR-STEM Integrated Cognitive Conflict-Based Physics Websites to Improve Critical Thinking and Remediation of Students' Misconceptions on Static Fluid - Himatul Azmi; Fatni Mufit; Hidayati Hidayati; Emiliannur emil; Yeka Hendriyani; Zahra Fathanah (Universitas Negeri Padang, 2026)
Critical thinking skills and conceptual understanding form a crucial foundation in physics education, enabling students to grasp abstract concepts, analyze various phenomena, and solve problems scientifically. However, low critical thinking skills and prevalent misconceptions regarding static fluids remain significant issues, necessitating instructional innovations that address both aspects. This study aimed to evaluate the effectiveness of an AR- and STEM-integrated, cognitive-conflict-based physics website in enhancing students' critical thinking skills and remediating misconceptions. A quantitative approach was employed quasi-experimental method with pre-test and post-test control group design. The study sample consisted of 68 Grade XI (Phase F) students from SMAN 2 Padang Panjang. Data were collected using a four-tier diagnostic test and analyzed through both descriptive and inferential statistics (specifically the Mann-Whitney test). The results indicated that students in the experimental class demonstrated superior critical thinking skills compared to those in the control class, while also exhibiting lower levels of misconceptions following instruction. The Asymp. Sig. (2-tailed) value of 0.000 (p<0.05) demonstrates that the AR-STEM-integrated, cognitive-conflict-based physics website is effective in enhancing critical thinking skills and remediating misconceptions regarding static fluids. This website holds potential as an alternative digital open resource to support physics learning